La inobservancia del principio de reserva de ley en la regulación del impuesto local a los espectáculos públicos vulnera el derecho a la seguridad jurídica del contribuyente - Ramón Quezada, María Fernanda (2021)
This thesis entitled: "THE INOBSERVANCE OF THE LAW RESERVATION PRINCIPLE IN THE REGULATION OF LOCAL TAX ON PUBLIC SPECTACLES VIOLATES THE RIGHT TO LEGAL SECURITY OF THE TAXPAYER", constitutes the final report of the investigation process carried out, and motivated by what Article 301 of the Constitution of the Republic of Ecuador states regarding the principle of legal reserve in tax matters that through the initiative of the Executive Branch and by means of a law approved by the National Assembly, taxes may be created, modified or suppressed, of the In the same way, within this section, it is emphasized that the rates and contributions will be created by legislative act of the competent body, that is, according to this article, a tax must be regulated by the legislator and by the sole and exclusive initiative of the President of the Republic. , the Constitution also empowers the Autonomous Decentralized Municipal Governments to create, modify, suppress and even exempt taxes, but only when it comes to taxes and contributions. Continuing, the principle of reserve of law is stipulated more clearly and precisely in the Ecuadorian Tax Code, establishing this as a general rule within tax matters and therefore any law that contains tax regulations must be subject to what is established in this legal body Thus, article 4 states that a tax law must contain the tax base, taxable object, active subject, taxpayer, the amount and exemptions, but at the time of regulating the tax on public shows in the Organic Code of Territorial Organization , Autonomy and Decentralization are not formally established these substantial elements of the tax, namely such as active subject, taxable person, generating event, being currently regulated through a municipal ordinance in each province and in each canton, generating confusion and uncertainty for the taxpayer of this tax that performs public shows due to the very fact that there is regulatory dispersion through ordinances that regulate certain basic elements that should be contained in the law, notably affecting the constitutional right to the legal security of the taxpayer, in this sense the legislator had to pay special attention to regulate within the Organic Code of Territorial Organization, Autonomy and Decentralization those elements that according to the Constitution and the Tax Code, due to the nature of this tax, the elements should be debated and approved by the National Assembly, in accordance with the principle of reservation of law.